EVALUASI PELAKSANAAN PROGRAM PELAYANAN MOBILE VOLUNTARY COUNSELLING AND TESTING (VCT) HIV DAN AIDS (Studi Kasus pada Perkumpulan Keluarga Berencana Indonesia (PKBI) Kota Semarang dan Lentera Asa Kota Semarang) - Elisra Prabawanti Mahadi; Zahroh Shaluhiyah; Emmy Riyanti (Jurnal Kesehatan Masyarakat (Undip), 2018)
Various efforts have been made to decrease the morbidity rate of HIV/AIDS in Indonesia, one of the program implemented is to carry out early detection to determine the status of someone already infected or not with HIV through Voluntary Counselling and Testing (VCT). Mobile clinic or mobile VCT is a strategy to increase the access of VCT with outreach the key population of HIV.The aim of this study is to describe the implementation of mobile voluntary counselling and testing held by Perkumpulan Keluarga Berencana Indonesia (PKBI) Semarang City and Lentera Asa Semarang City.This research is a descriptive research with qualitative approach. This research data is collected by using in-depth interviews with mobile VCT providers and mobile VCT clients from both NGOs who become the case study of this research.In this research it was found that both NGOs starts carrying out mobile VCT with outreach, pre-testing counselling, HIV testing, post-testing counselling and sustainable support services. PKBI Semarang City implements mobile VCT by involving government health services or also their self-support clinic which is Griya Asa Clinic. In mobile VCT implementation organized by PKBI Semarang City, the counselling services not only done by professional counselors but also done by lay counselors who is in charge as field officers. In mobile VCT implementation organized by Lentera Asa Semarang City, all the VCT services provided by government health services but there were no certified case manager from institution. PKBI Semarang City has mobile VCT data collection in the form of each implementation and monthly report while Lentera Asa performs data collection in the form of cumulative data collection. There is a need of repetitive review for the service providers’s qualifications and data collection of mobile VCT implementation.